2017
DOI: 10.1021/acs.bioconjchem.7b00146
|View full text |Cite
|
Sign up to set email alerts
|

“Bottom-up” Construction of Multi-Polyprodrug-Arm Hyperbranched Amphiphiles for Cancer Therapy

Abstract: Despite the great advantages of polymer-drug conjugates (PDC) in cancer therapy, control of the drug loading site and degree via a facile approach remains a great challenge. Herein, by combining the controllability of the "bottom-up" strategy and the stability of multiarm hyperbranched amphiphiles, we have developed novel multi-polyprodrug-arm hyperbranched amphiphiles (H40-star-(PHCPTMA-b-PMPC), hPCM) via reversible addition-fragmentation chain transfer (RAFT) polymerization for cancer therapy. The hPCM was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 53 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…Attractively, the hPAs can not only be used for drug delivery but also be applied as MR (magnetic resonance) imaging contrast agents for cancer imaging because of the introduction of the Gd complex. In addition, RAFT polymerization has also been adopted to prepare multi‐polyprodrug‐arm hyperbranched amphiphiles (Figure b) . The drug‐loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent.…”
Section: Drug‐delivery Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attractively, the hPAs can not only be used for drug delivery but also be applied as MR (magnetic resonance) imaging contrast agents for cancer imaging because of the introduction of the Gd complex. In addition, RAFT polymerization has also been adopted to prepare multi‐polyprodrug‐arm hyperbranched amphiphiles (Figure b) . The drug‐loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent.…”
Section: Drug‐delivery Applicationsmentioning
confidence: 99%
“…In addition, RAFT polymerization has also been adopted to preparem ulti-polyprodrug-arm hyperbranched amphiphiles (Figure 9b). [48] The drug-loading content can be conveniently tuned by adjusting the feed ratio of the prodrug to macroRAFT agent. Duan et al [49] have recently reported the direct preparation of ah yperbranched polyprodrug by using drug molecules as polymericm onomers with drug-loading contentso f2 2a nd 24 %.…”
Section: Drug Conjugation By Using the Drug As Ap Olymeric Monomermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, optimal water solubility has been achieved by introducing a pH-sensitive cleavable linker and target moiety to a multi-arm copolymer and ultimately complexing it with viral particles. 74 , 75 …”
Section: The Host Complex and Viral Vector Bioavailabilitymentioning
confidence: 99%
“…Free drugs are designed to be polymerizable for constructing the polymer skeleton as repeating prodrug units through stimuli‐responsive linkages between drug molecules and polymer backbone, therefore, considerable portion of drugs (even up to >50 wt%) in the whole complex could be feasible. Moreover, the drug loading amount can be facilely modulated by tuning the feed ratio of chain transfer agent/prodrug monomer during polymerization …”
Section: Introductionmentioning
confidence: 99%